2019
DOI: 10.24331/ijere.573870
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parents in Improving the Behavior of School’s Students in Azena Primary School, Ethiopia

Abstract: The major purpose of this study is to investigate the role of parents in shaping students' behavior in Azena primary school (primary first cycle (Grade 1-4) and primary second cycle (Grade 5-8)). The study was descriptive in nature. 40 teachers were selected through census survey method for questionnaire and 10 parents were selected for key informant interview purposively. The collec ted data were analyzed and interpreted using simple descriptive statistical tools, frequency and percentage. This study reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Mathematics is a difficult subject for students. Similar with Yigzaw (2019), the parents contribution in improving students' school behavior is low because of the lack of proper training strategies and poor interactions between home and school, and also unoptimal parental monitoring. Bashir (2014) in his research stated that the school environment has a bigger influence on student Mathematics performance than the home environment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mathematics is a difficult subject for students. Similar with Yigzaw (2019), the parents contribution in improving students' school behavior is low because of the lack of proper training strategies and poor interactions between home and school, and also unoptimal parental monitoring. Bashir (2014) in his research stated that the school environment has a bigger influence on student Mathematics performance than the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on preliminary studies researchers found that teachers are unoptimal in the innovation of teaching and learning so students find it difficult to capture the subject matter essence. Yigzaw (2019) in his research found that poor teaching methods, and inadequate school facilities resulted in student school low behavior. Therefore, the lack of facilities makes the teacher performance un-optimal, and this requires teachers' creativity and innovation in Mathematics learning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations